Western blot analysis of tick antigens from a Rhipicephalus sanguineus unfed larval extract and identification of antigenic sites in tick sections using immunohistochemistry. A comparative study between resistant and susceptible host species - Ferreira, B. R. [UNESP]; Machado, R. Z. [UNESP]; Bechara, G. H. [UNESP] (Elsevier, 1996)
Most parasite-host relationships are characterized by the development of resistance by the host, thus limiting the number of parasites. However, some cases are very unusual. In the relationship of the domestic dog with the brown dog-tick Rhipicephalus sanguineus this does not occur, whereas guinea pigs develop efficient resistance. Sera from domestic dogs, crab-eating foxes and guinea pigs collected before and after infestation with R. sanguineus ticks, and after immunization with a whole tick adult or larval homogenate, were used in Western blot analysis to compare and identify potential important antigens from a tick larval homogenate. The same sera were tested in an indirect immunohistochemistry assay in an attempt to compare relevant antigenic sites on histological tick sections. The immunoblotting displayed antigens recognized only by the guinea pigs, as well as several shared antigens between host species, depending on the kind of immunization. Immunohistochemistry revealed probable antigenic sites on the cells and tissues of ticks, which varied depending on the kind of immunization (infestation or vaccination) and the animal species involved.
Keywords: Crab-eating fox; Dog; Guinea pig; Immunization-Arthropoda; Immunohistochemistry; Rhipicephalus sanguineus; Western blot; parasite antigen; animal experiment; controlled study; dog; fox; guinea pig; host parasite interaction; host resistance; immunization; immunoblotting; immunohistochemistry; larva; nonhuman; tick; Animals; Antigen-Antibody Complex; Antigens; Blotting, Western; Dogs; Foxes; Guinea Pigs; Host-Parasite Relations; Immunization; Larva; Tick Infestations; Ticks; Acari; Animalia; Arthropoda; Canidae; Canis familiaris; Canis lupus; Cavia; Cavia porcellus; Decapoda (Crustacea); Dusicyon thous; Sus scrofa